OCCUPATIONAL CONTACT DERMATITIS IN HAIRDRESSERS - Komang Ayu Kristiana Dewi K; Luh Made Mas Rusyati; IGK Darmada (E-Jurnal Medika Udayana, 2013)
Occupational skin disease is a skin disease caused or aggravated by work. Occupational skin disease experienced by most hairdressers are contact dermatitis, both irritant and allergic. Some examples of materials that can cause contact dermatitis in hairdressers are nickel, formaldehyde, ammonium thioglycolate, and p-phenylenediaminz. Diagnosis of contact dermatitis in hairdressers enforced through anamnesa, physical examination, and additional tests that are relevant include patch test. The most important treatment is to avoid exposure to irritants and eliminate factors that aggravate. Where appropriate, to address the inflammation can be given topical corticosteroids, such as hydrocortisone.